A high-resolution Late Glacial to Holocene record of environmental change in the Mediterranean from Lake Ohrid (Macedonia/Albania) - Lacey, Jack H.; Francke, Alexander; Leng, Melanie J.; Vane, Christopher H.; Wagner, Bernd (SPRINGER, 2015)
Lake Ohrid (Macedonia/Albania) is the oldest extant lake in Europe and exhibits an outstanding degree of endemic biodiversity. Here, we provide new high-resolution stable isotope and geochemical data from a 10 m core (Co1262) through the Late Glacial to Holocene and discuss past climate and lake hydrology (TIC, delta C-13(calcite), delta O-18(calcite)) as well as the terrestrial and aquatic vegetation response to climate (TOC, TOC/N, delta C-13(organic), Rock Eval pyrolysis). The data identifies 3 main zones: (1) the Late Glacial-Holocene transition represented by low TIC and TOC contents, (2) the early to mid-Holocene characterised by high TOC and increasing TOC/N and (3) the Late Holocene-Present which shows a marked decrease in TIC and TOC. In general, an overall trend of increasing delta O-18(calcite) from 9 ka to present suggests progressive aridification through the Holocene, consistent with previous records from Lake Ohrid and the wider Mediterranean region. Several proxies show commensurate excursions that imply the impact of short-term climate oscillations, such as the 8.2 ka event and the Little Ice Age. This is the best-dated and highest resolution archive of past Late Glacial and Holocene climate from Lake Ohrid and confirms the overriding influence of the North Atlantic in the north-eastern Mediterranean. The data presented set the context for the International Continental scientific Drilling Program Scientific Collaboration On Past Speciation Conditions in Lake Ohrid project cores recovered in spring-summer 2013, potentially dating back into the Lower Pleistocene, and will act as a recent calibration to reconstruct climate and hydrology over the entire lake history.